Research trends in different social media platform and body image - Wang, Zijun; Kasimon, Diyana; Wan Abas, Wan Anita; Ma, Yueshi; Ruan, Qijie (Human Resource Management Academic Research Society, 2023)
This review will critically analyse the impact of short social media videos on body image. This review focuses specifically on the perception of social media and body image and the impact of different social media platforms on users' body image. It was found that there are positive (Trekels et al., 2018; Gilmour et al., 2020) and negative (Cohen & Blaszczynski, 2015; Yurdagül et al., 2021) effects on body image when people use social media. And, social comparison is one of the essential factors influencing the impact of social media on body image (Rahmadiansyah, 2022). Furthermore, the impact of social media on body image is stronger than that of traditional media. Furthermore, among social media, those based on sharing videos have a greater impact on body image than those based on images and texts (Engeln et al., 2020). However, there are still many limitations to the impact of social media on body image, and further research is needed to determine the specific impact of social media on body image, taking into account the characteristics, content, functions and tools of different social media platforms, as well as user thinking and cultural contextual factors.